Cellular Dermatofibroma: Clinicopathologic Review of 218 Cases of Cellular Dermatofibroma to Determine the Clinical Recurrence Rate. Issue 11 (November 2019) - Gaufin, Meredith; Michaelis, Timothy; Duffy, Keith
Abstract : BACKGROUND: Cellular dermatofibromas, a variant of dermatofibroma, are reported to recur at rates of 26% to 50%. OBJECTIVE: To determine whether there are distinct clinical or histological differences between cellular dermatofibromas that recur versus those that do not. To determine recurrence rates in a real-world clinical setting. MATERIALS AND METHODS: A retrospective analysis of the medical records and skin biopsies of cellular dermatofibroma in the University of Utah Health system between December 2011 and 2016. Clinical and dermatopathological features were evaluated to find distinct differences between the cellular dermatofibromas that recurred compared with those that did not. RESULTS: There were no significant differences in histology between the primary lesions in recurrent and nonrecurrent cases. One factor that seemed to be associated with a greater likelihood of recurrence was an initial lesion size greater than 1 cm. The authors' data suggest that if the margins are involved on initial biopsy, there is a 10% chance of recurrence. This percentage is far less than the 26% to 50% reported in the past literature. CONCLUSION: If a patient presents with a cellular dermatofibroma larger than 1 cm and positive margins at initial biopsy, a careful discussion should be had between the provider and patient about the low risk of local recurrence.